Uncommon Cause of Right Upper Quadrant Pain Treated by Laparoscopic Surgery: A Case Report - Feng, Qingbo; Du, Jinpeng; Liao, Wenwei; Zheng, Jinli; Zeng, Yong; Li, Jiaxin (Frontiers in Surgery, 2022)
Introduction Right upper quadrant pain is a very common symptom of cholecystitis. Right upper quadrant pain caused by fish bone perforation of the stomach wall is rare. Case Presentation We report a 42-year-old woman who was admitted to our hospital with “1-month history of dull progressive right upper quadrant pain radiating to the back.” Computed tomography of the abdomen revealed a linear, high-density body between the stomach wall and the liver. On history, the patient stated she had eaten a bony fish a month prior but did not note any significant pain at the time. Laparoscopy revealed a fish bone 2 cm in length half on the surface of the caudate lobe of the liver, and no perforation of the gastrointestinal tract was found. The postoperative course was uncomplicated, and the patient was discharged home on day 3 after surgery. Conclusion The case of right upper quadrant pain caused by the fish bone is very rare. Radiological examinations play a significant role in the diagnosis of fish bone ingestion. Laparoscopic surgery is technically feasible and safe for the treatment of patients with fish bone ingestion.